Quality by Design Approach for Fabrication of Rifampicin-Loaded Solid Lipid Nanoparticles: Effect on Formulation and Characteristic Parameters - Mohanta, Bibhash C. (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Rifampicin (RIF), a first-line anti-tuberculosis drug having an inimitable potential of rapidly killing mycobacterium. Unfortunately, it has poor bioavailability, short half-life period (t1/2), and intense toxicity. To solve the problem, solid lipid nanoparticles (SLN) of RIF were developed by high-pressure homogenization followed by ultrasonication technique. Objectives: The objective of this work was to understand the process variables and their effect on formulation aspects through an experimental approach and to optimize the formulation with the application of response surface methodology. Materials and Methods: The quality by design of 3(2) factorial was employed for the optimization of the formulation. The concentration of stearic acid (SA), lecithin, and poloxamer (POL) was considered as an independent factor, and their impact on particle size (PS), entrapment efficiency (%EE), and cumulative drug release (%CDR) was investigated. Results and Discussion: It was found that SA and lecithin had a positive impact, but POL had a negative impact on PS and %EE. The %CDR was positively influenced by lecithin and POL concentration, whereas it was negatively influenced by SA concentration. The average PS, zeta potential, and %EE of the optimized formulation were found to be 172.5 nm, −025.6 mV, and 70.34%, respectively. The optimized formulation showed a %CDR of 64.34% in 96 h, and the drug release pattern followed non-Fickan kinetics. X-ray diffraction study revealed large amorphousness nature of RIF in SLNs. Scanning electron microscopy study reported spherical shaped nanometric size particles. It was revealed from the stability study that the developed RIF-SLNs were stable at 4 ± 2°C when compared with their storage at 25 ± 2°C/60 ± 5% RH in 6 months of storage period. Conclusions: These results implied that the prepared RIF-SLNs could improve bioavailability and reduce toxicity for effective tuberculosis therapy.